A Study to Assess the Effectiveness of Planned Teaching Programme on Knowledge Regarding Blood Donation among College Students at Selected Arts Colleges Banaskantha, Gujaratmong College Students at Selected Arts Colleges Banaskantha, Gujarat - Upadhyay, Rishabh; Varghese, Jibin; Parmar, Raymal; Parmar, Amrut; Bhil, Vishnu; Bhiladiya, Bhoomika; Chaudhar, Vimu; Chaudhary, Varsha (International Journal of Nursing Research, 2024)
Background: Blood donation (BD) is an essential and integral part of our fitness care system. Without BDs, various scientific techniques that we take with no consideration could not take place. BDs enable medical professionals to perform a wide range of life-saving procedures. Methods: This study used a quantitative research methodology with a pre-experimental one-group pre-test post-test research design. By employing the non-probability purposive sampling approach, 60 college students were chosen. Explain about BD self-administered questionnaire was used for the pre-test on the 1st day. On the 7th day, a post-test was conducted using a self-administered questionnaire to determine the impact of the planned teaching on college students’ knowledge about BD. Both descriptive and inferential statistical methods, including frequency, percentage, and Chi-square, were used to examine and interpret the data that had been collected. Results: According to the results, just 5% of respondents had adequate knowledge about BD, 33.33% had moderate knowledge, and 61.66% had inadequate knowledge. The mean score of post-test knowledge score of 16.63 (68.22%) is higher than the mean pre-test knowledge score of 7.03 (32.78%), the enhancement in the knowledge of respondents was 9.6 (35.44%) suggesting that the planned teaching program was effective in increasing the knowledge of college student regarding BD among. The data also show that at a significance level of 0.05, the “z” value of 13.18 is significantly greater than the table value of 1.96. Conclusion: The planned teaching program significantly enhanced college students’ knowledge of BD.